2021
DOI: 10.1007/s00213-021-05771-5
|View full text |Cite
|
Sign up to set email alerts
|

Functional observation after morphine withdrawal: effects of SJP-005

Abstract: Rationale and objective SJP-005 (ketotifen and ibuprofen) is being developed as a potential new treatment for opioid withdrawal. Three studies were conducted to evaluate the early phase (acute, day 1) and late phase (days 2–12) effects of SJP-005 on discontinuation-induced morphine withdrawal. Methods Sprague-Dawley rats received subcutaneous morphine twice daily for 18 days and ceased on day 19. Twice daily, oral dosages of placebo or SJP-005 (1 mg/kg ket… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…This effect was significant in the late phase of withdrawal (2-12 days after withdrawal) when SJP-005 was administered two days before morphine cessation. In addition, the number of days it took to observe zero withdrawal signs was significantly shorter when SJP-005 was administered two days before morphine cessation [12]. Taken together, these findings suggest that SJP-005 is a suitable candidate drug to be used for opioid withdrawal, and it deserves further investigation.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…This effect was significant in the late phase of withdrawal (2-12 days after withdrawal) when SJP-005 was administered two days before morphine cessation. In addition, the number of days it took to observe zero withdrawal signs was significantly shorter when SJP-005 was administered two days before morphine cessation [12]. Taken together, these findings suggest that SJP-005 is a suitable candidate drug to be used for opioid withdrawal, and it deserves further investigation.…”
Section: Introductionmentioning
confidence: 77%
“…SJP-005, a new product that is being developed as a pain treatment and for opioid use disorder, is a combination product of an antihistamine drug with Toll-like receptor 4 (TLR4) inhibition properties (ketotifen), and a non-steroidal anti-inflammatory drug (NSAID) which also possesses peroxisome proliferator-activated gamma receptor (PPAR-γ) agonist activity (ibuprofen) [10,11]. Previous research in rodents [12] suggests that SJP-005 is effective in significantly reducing opioid withdrawal signs after cessation of morphine treatment. In three studies, rats were treated twice daily for 19 days with morphine.…”
Section: Introductionmentioning
confidence: 99%
“…Another NSAID/antihistamine drug combination (SJP -005, the combination of ibuprofen and ketotifen) showed to be effective in significantly reducing the incidence and duration of discontinuation-induced morphine withdrawal symptoms in rats, when treatment was initiated 2 days before morphine cessation. 30 A second study found that rats could withstand higher levels of painful stimuli when SJP-005 was co-administered, suggesting a possible opioid sparing effect. 31 A synergistic effect was demonstrated in a preclinical study demonstrating the effectiveness of another NSAID/antihistamine drug combination (SJP -002C, the combination of indomethacin and ketotifen) in inhibiting 2019 coronavirus replication.…”
Section: Discussionmentioning
confidence: 99%
“…It is thought that the anti‐inflammatory effect of the NSAID is strengthened by the mast cell stabilizing effects of the antihistamine drug. Another NSAID/antihistamine drug combination (SJP – 005, the combination of ibuprofen and ketotifen) showed to be effective in significantly reducing the incidence and duration of discontinuation‐induced morphine withdrawal symptoms in rats, when treatment was initiated 2 days before morphine cessation 30 . A second study found that rats could withstand higher levels of painful stimuli when SJP‐005 was co‐administered, suggesting a possible opioid sparing effect 31 .…”
Section: Discussionmentioning
confidence: 99%
“…The users potentially succumb to dependence due to the severity of the withdrawal symptoms including abdominal pain, nausea, diarrhea, lacrimation, and generalized piloerection. In contrast to the drug pain-relieving effects, drug cessation in the morphine-dependent state results in the genesis of negative effects such as anxiety, agitation, and dysphoria ( Verster et al, 2021 ). Psychological dependence on the other hand refers to the state of the patient where they are craving for the drug, to relieve its withdrawal symptoms, or for its gratifying effects ( Jacobs, 1986 ).…”
Section: Opioid Use Disordermentioning
confidence: 99%